(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Emotional self-regulation of behavior is the ability to emotionally respond to life events in a socially acceptable way, while maintaining sufficient flexibility to allow spontaneous reactions, but postpone them if necessary. Externally observable signs that can be used to draw a conclusion about a person’s ability to emotional self-regulation of behavior are: the rate of speech, muscle tone, heart rate, breathing, complexion